Impact of wellness indicators in the relationship between external and internal load in football - Chassard, T.; Dormion, G.; Dupuit, M.; Blanquet, L.; Meignie, A.; Halladja, A.; Toussaint, J. F.; Antero, J. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Understanding the relationship between external and internal load according to the wellness monitoring commonly used in elite sports can be of great interest in order to adapt and optimise the athletes` training sessions. We aimed to determine whether the external load performed in a training session is below or above what is expected for an athlete considering a specific internal load, based on the athletes` individual profile, and then to identify the wellness parameters that may be associated with these variations.